2020
DOI: 10.1016/j.heliyon.2020.e03757
|View full text |Cite
|
Sign up to set email alerts
|

Oral intake of Streptococcus thermophilus improves knee osteoarthritis degeneration: A randomized, double-blind, placebo-controlled clinical study

Abstract: This preliminary clinical study demonstrates the possibility of a new species of probiotic for improvement of the degeneration of knee osteoarthritis (KOA). TCI633 (Streptococcus thermophilus) is a newly founded bacterium from human breast milk, and it is able to produce hyaluronate (HA) in gastrointestinal (GI) tract. A recent study has proved that TCI633 can substantially alleviate synovial tissue inflammation and cartilage damage in the animal models, but so far it has never been applied in clinical interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The effects of S. thermophilus have been studied in experimental OA, and in actual patients. Oral intake of Streptococcus thermophiles improves knee osteoarthritis degeneration [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of S. thermophilus have been studied in experimental OA, and in actual patients. Oral intake of Streptococcus thermophiles improves knee osteoarthritis degeneration [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been fewer such studies related to OA in comparison to RA or IBD, the effect has been confirmed in several strains. Lactobacillus casei strain Shirota, Lactobacillus acidophilus , and Streptococcus thermophilus were applied to experimental models of OA and clinically applied in patients and shown to be effective [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated the e cacy of applying L. acidophilus in MIA-induced OA [10]. The effects of S. thermophilus have been studied in experimental OA, and in actual patients [11]. Several recent reports have described the therapeutic effects of the administration of probiotics and prebiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been fewer such studies related to OA in comparison to RA or IBD, the effect has been con rmed in several strains. Lactobacillus casei strain Shirota, Lactobacillus acidophilus, and Streptococcus thermophilus were applied to experimental models of OA and clinically applied in patients and shown to be effective [8][9][10][11] Lactobacillus rhamnosus is known to produce butyrate, a short chain fatty acid (SCFA), through alteration of the gut microbiota. Therefore, L. rhamnosus may have an immunomodulatory effect and a protective effect on cartilage [12,13], suggesting that L. rhamnosus may be another probiotic strain with a therapeutic effect on OA.…”
Section: Introductionmentioning
confidence: 99%
“… 169 In another recent investigation, supplementation with another probiotic strain ( Streptococcus thermophiles versus placebo) resulted in reductions in CRP and markers indicating degradation of type II collagen, but had no effect on WOMAC. 170 Additional research is needed to enhance our understanding of the effects of probiotics in patients with different types of arthritis, while considering potential confounding factors, including age, sex, diet, medications and individual microbial signatures.…”
Section: Prebiotics and Probiotics For The Modulation Of Gut Microbiome And Musculoskeletal Health In Humans (Adults)mentioning
confidence: 99%